Dual-Server Identity-Based Encryption with Authorized Equality Test for IoT Data in Clouds. (11th October 2022) - Zhao, Meng; Ding, Yong
Abstract : The massive amounts of data collected by Internet of things (IoT) devices can be stored in clouds to solve the problem of the low storage capacity of IoT terminals. However, the privacy and security of outsourced IoT data may be compromised on the cloud side. Traditional cryptographic technologies can protect data privacy but require the user to retrieve the data for decryption and further processing, which would bring vast amounts of bandwidth and computation burden to users. This paper proposes a dual-server identity-based encryption scheme supporting authorized ciphertext equality test (DS-IBE-AET), where two noncolluding servers with authorizations from users can collaboratively carry out an equality test on outsourced IoT ciphertexts without decrypting the data. DS-IBE-AET can resist offline keyword guessing attacks confronted by existing encryption schemes with equality test in the single server model. Security analysis demonstrates that the proposed DS-IBE-AET scheme offers unforgeability for private keys of users and servers and confidentiality protection for outsourced IoT data and authentication tokens. The performance analysis indicates the practicality of our DS-IBE-AET construction for securing outsourced IoT data in clouds.